1976
DOI: 10.1002/jss.400040407
|View full text |Cite
|
Sign up to set email alerts
|

Substrate heterogeneity of component a of the human erythrocyte membrane

Abstract: Component a of the erythrocyte membrane is a specific substrate for endogenous protein kinase activity and its phosphorylation is significantly decreased under assay conditions in myotonic muscular dystrophy (Roses, A.D., and Appel, S.H.J. Membr. Biol 20:51-58 (1975)). We have demonstrated substrate heterogeneity of two fractions of component a separated by concanavalin A (Con-A) sepharose chromatography. The fraction of component a that is retarded by Con A and eluted with alpha-methyl-D-glucoside does not ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…No differences could be demonstrated in the level of acyl phosphorylation in MyD erythrocytes (A. D. Roses, unpublished data), but a definite decrease was noted in the ester phosphorylation of serine and threonine in band III . Whether the specific component of band III, in which the difference in phosphoserine and phosphothreonine formation occurs, is also the Na+ K+ ATPase or some other constituent is still under investigation (Roses, 1975). This possible alteration of Na+ K+ ATPase phosphorylation suggested the ionic flux experiments reported here.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…No differences could be demonstrated in the level of acyl phosphorylation in MyD erythrocytes (A. D. Roses, unpublished data), but a definite decrease was noted in the ester phosphorylation of serine and threonine in band III . Whether the specific component of band III, in which the difference in phosphoserine and phosphothreonine formation occurs, is also the Na+ K+ ATPase or some other constituent is still under investigation (Roses, 1975). This possible alteration of Na+ K+ ATPase phosphorylation suggested the ionic flux experiments reported here.…”
Section: Discussionmentioning
confidence: 70%
“…Our previous biochemical and biophysical studies suggested that the disease could be best understood as a cell membrane alteration with independent expression in several tissues (Roses & Appel, 1973; Butterfield, Chesnut, Roses & Appel, 1974a; Butterfield, Roses, Cooper, Appel & Chesnut, 1974b. ; Roses & Appel, 1974, 1975 Miller, . This concept has been supported by the findings of other investigators in a wide variety of human and murine muscular dystrophies.…”
Section: Introductionmentioning
confidence: 99%
“…The present studies represent one of a series of experiments using several lectins including Concanavalin A, Ricin II, and wheat germ agglutinin. None of these other lectins yielded a fraction that showed a difference in phosphorylation in MyD membranes as compared to controls (Roses, 1976).…”
Section: Discussionmentioning
confidence: 92%
“…The carbohydrate moieties of the major sialoglycoprotein have been shown to vary, depending on the age of the erythrocyte cells (Marikovsky, Danon & Katchalsky, 1966;Balduini & Ascari, 1974). Carbohydrate heterogeneity may also be an explanation for the Band 3 glycoprotein since affinity chromatography with the lectin, Concanavalin A (Roses, 1976;Findlay, 1974), and the binding of *25I-Concanavalin A to the electrophoretic region of migration of Band 3 (Kawaguchi & Osawa, 1976) have demonstrated that Concanavalin A can interact with only a fraction of Band 3 (approximately 30%). The use of galactose oxidase with tritiated sodium borohydride also indicated a carbohydrate heterogeneity in proteins of Band 3 since the peak of incorporation of tritium in the electrophoretic region of migration of isolated Band 3 lags slightly behind the Coomassie blue peak of Band 3 (Yu & Steck, 1975a).…”
Section: Discussionmentioning
confidence: 97%
“…1 and references contained therein). Glycophorin is the human erythrocyte receptor for influenza virus and several lectins, and carries the M/N blood group determinants (2), while a subpopulation of band 3 is the concanavalin A (Con A) receptor (3,4).…”
mentioning
confidence: 99%